Esophageal cancer: Risk factors, screening and endoscopic treatment in Western and Eastern countries - Arnal, María José Domper (World journal of gastroenterology : WJG, 2015)
Esophageal cancer is one of the most unknown and deadliest cancers worldwide, mainly because of its extremely aggressive nature and poor survival rate. Esophageal cancer is the 6(th) leading cause of death from cancer and the 8(th) most common cancer in the world. The 5-year survival is around 15%-25%. There are clear differences between the risk factors of both histological types that affect their incidence and distribution worldwide. There are areas of high incidence of squamous cell carcinoma (some areas in China) that meet the requirements for cost-effectiveness of endoscopy for early diagnosis in the general population of those areas. In Europe and United States the predominant histologic subtype is adenocarcinoma. The role of early diagnosis of adenocarcinoma in Barrett's esophagus remains controversial. The differences in the therapeutic management of early esophageal carcinoma (high-grade dysplasia, T1a, T1b, N0) between different parts of the world may be explained by the number of cancers diagnosed at an early stage. In areas where the incidence is high (China and Japan among others) early diagnoses is more frequent and has led to the development of endoscopic techniques for definitive treatment that achieve very effective results with a minimum number of complications and preserving the functionality of the esophagus.